2016
DOI: 10.14781/mcd.08328
|View full text |Cite
|
Sign up to set email alerts
|

Üni̇versi̇te Öğrenci̇leri̇ni̇n Türk Dünyasi Coğrafyasina İli̇şki̇n Farkindalik Düzeyleri̇ni̇n Beli̇rlenmesi̇

Abstract: ÖZET Gelecekte devletin çeşitli kademelerinde görev yapacak olan üniversite öğrencilerinin Türk Dünyası ile Türkiye arasındaki ilişkileri daha ileri götürebilecek konumda olabilmesi için Türk Dünyası Coğrafyasına ilişkin farkındalıklarının büyük önem arz ettiği düşünülmektedir.Üniversite öğrencilerinin Türk Dünyası Coğrafyası farkındalık düzeylerinin belirlenmesi çalışılmanın amacını oluşturmaktadır. Çalışmada veri toplama aracı olarak üç bölümden oluşan anket formu kullanılmıştır.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0
8

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 0 publications
2
7
0
8
Order By: Relevance
“…To sum up, the findings of this study is similar with the literature in terms of low knowledge level of students about Turkic world (Bayram, 2011;Topal and Sezer, 2016;Tunçel, 2002). Also, this study is in parallel with other studies in terms of the wholeness of Turkic world (Ulusoy, 2009) and Turkey's key role in unifying these countries (Çoban and Temir, 2017).…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…To sum up, the findings of this study is similar with the literature in terms of low knowledge level of students about Turkic world (Bayram, 2011;Topal and Sezer, 2016;Tunçel, 2002). Also, this study is in parallel with other studies in terms of the wholeness of Turkic world (Ulusoy, 2009) and Turkey's key role in unifying these countries (Çoban and Temir, 2017).…”
Section: Discussionsupporting
confidence: 89%
“…As noted in findings, significant differences have been observed in the way prospective social studies teachers looked at topics and concepts and in their knowledge level after they attended a course on the Turkic World. This is also the case in the study by Topal and Sezer (2016) titled "Determining the awareness level of university students about the geography of the Turkic world". Data was collected from 800 university students in total, 258 of which were from education faculties.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…And there has been no study observed in the literature that is performed with WAT to reveal students' perceptions on the Turkic world. Alım [35] detected the Geography Education students' perceptions of the Turkic World with the knowledge test and open-ended questions; Aksoy and Karaçalı [36] wanted to learn about seventh-grade students' perception of the Turkic World on their mind map by asking them to find those countries on the dummy map; and Topal and Sezer [37] found about university students' levels of awareness of the Turkic World geography with map and flag knowledge along with the open-ended questions. Other than these studies, Tuncel [38] tried to reveal students' perceptions of Islam in their minds by drawing a map; Bilgiç and Akyürek [39] examined Balkan-origin students' perceptions of Turkey in Balkans and the Turks; and Alkan [40] examined university students' perceptions of the European Union in Turkey.…”
Section: Introductionmentioning
confidence: 99%